Attitudes Towards Appearance and Body-Related Stigma Among Young Women With Obesity and Psoriasis - Mazurkiewicz, Natalia; Krefta, Jarosław; Lipowska, Małgorzata (Frontiers in Psychiatry, 2021)
The goal of this study was to investigate the role of the subjective assessment of one’s body image in the relationship between objective indices of appearance and perceived stigma in young women affected by obesity and psoriasis. These are chronic diseases that decrease one’s physical attractiveness and are associated with stigma related to body defects. A total of 188 women in early adulthood took part in the study (M = 25.58; SD =2.90), including obese women (n = 54), women suffering from psoriasis (n = 57), and a control group (n = 77). The participants filled the Multidimensional Body-Self Relations Questionnaire, Perceived Stigmatization Questionnaire, and a socio-demographic questionnaire. Anthropometric data were gathered using a body composition analyzer. Objective parameters of body shape were calculated (WHR and ICO). Subjective assessment of one’s body and attitudes towards one’s body were found to influence perceived stigma, independently of the condition causing the stigma and of the objective appearance of the participant. This study did not support the existence of a relationship between parameters regarding body shape and sense of stigma, even when subjective body assessment acted as a moderator. At the same time, body mass was a strong predictor of the levels of perceived stigma. Women affected with obesity perceived a higher level of stigma, than the remaining groups. The severity of psoriasis did not impact the perceived stigma. Moreover, women with psoriasis assessed their health – as a part of the assessment of their bodies – the highest, which may explain the lower perceived stigma in this group.